1992
DOI: 10.1128/mcb.12.11.4852
|View full text |Cite
|
Sign up to set email alerts
|

Elements responsible for hormonal control and tissue specificity of L-type pyruvate kinase gene expression in transgenic mice.

Abstract: L-tpe pyruvate kinase (L-PK) is a key enzyme of the glycolytic pathway specifically expressed in the liver and, to a lesser degree, in the small intestine and kidney. One important characteristic of L-PK gene expression is its strong activation by glucose and insulin and its complete inhibition by fasting or glucagon treatment.Having previously established that the entire rat L-PK gene plus 3.2 kbp of 5'-flanking region functions in mice in a tissue-specific and hormonally regulated manner, various deletions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…With brain extracts, the A footprint (-197 to -171) was shifted to the 5' side and began on the 3' side at the same nucleotide as a faint footprint resulting from protection by recombinant Krox2O/Krox24 proteins. In gel retardation experiments, oligonucleotide NA', however, formed a single very faint complex with brain nuclear pro- CAT activity was determined with 50 pg tissue extracts previously heated for 20 min at 60°C to destroy tissue deacetylase activity (Cuif et al, 1992). B, brain; I, intestine; M, muscle; H, heart; K, kidney; S, spleen; T, testes; L, lung; Li, liver.…”
Section: Discussionmentioning
confidence: 99%
“…With brain extracts, the A footprint (-197 to -171) was shifted to the 5' side and began on the 3' side at the same nucleotide as a faint footprint resulting from protection by recombinant Krox2O/Krox24 proteins. In gel retardation experiments, oligonucleotide NA', however, formed a single very faint complex with brain nuclear pro- CAT activity was determined with 50 pg tissue extracts previously heated for 20 min at 60°C to destroy tissue deacetylase activity (Cuif et al, 1992). B, brain; I, intestine; M, muscle; H, heart; K, kidney; S, spleen; T, testes; L, lung; Li, liver.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with transgenic mice indicated that this region confers tissue-specificity to L promoter activity [77][78][79]. The promoter (-183 to +11) contains binding sites for HNF-1, NF-I, HNF-4, upstream stimulating factor (USF)-related proteins and L5-binding factors (Figure 1) [80][81][82][83].…”
Section: Tissue-specific Controlmentioning
confidence: 99%
“…The binding of HNF-4 apparently stabilizes NF-I binding [80]. The promoter corresponds to a liver-specific DNAase I-hypersensitive site HSS-1 [85] and suffices to confer tissue-specificity in vitro as well as in transfection and in transgenic mice [79,81,86,87]. The most potent transcriptional stimulators are the liver-specific factors HNF-I and HNF-4.…”
Section: Tissue-specific Controlmentioning
confidence: 99%
See 2 more Smart Citations